Pendidikan Islam Di Indonesia: Problem Masa Kini Dan Perspektif Masa Depan - Vita Fitriatul Ulya (Al Hikmah: Jurnal Studi Keislaman, 2018)
Abstract: Today, globalization is seen as an irresistible force that provides economicprosperity to people throughout the world. But on the other hand, he was accused ofbeing the source of all contemporary diseases, especially Islamic education in Indonesia.The problem of Islamic education that is happening today actually refers more to thechallenges of Islamic education institutions in overcoming the destruction of the pillars ofthe nation's character. While the challenge that must be faced by Islamic education is interms of education management, a plan for future education must cover three maincharacteristics of society, namely the future of socio, the future of techno and the futureof bio, with all its implications and impacts on the human soul. As stated that one of theobjectives of Islamic education is to create a generation that has strength both in faithand mastery of science and technology. So Islamic education must be able to adjust to thedevelopment and demands of the times. Islamic education has presented itself aseducation that is flexible, responsive, in line with the times, oriented towards the future,balanced, oriented to superior quality, fair, democratic, dynamic and so on. Somealternative solutions that can be done, among others, are the new paradigm of Islamiceducation must be based on theocentric and anthropocentric philosophy at the same time,Islamic education is able to build scientific and educational progress that is integrativebetween spiritual, moral and material values for human life. Keyword, Islamic Education, Islamic education in Indonesia, and responsive